Retrospective analysis of pulse oximeter alarm settings in an intensive care unit patient population. Issue 1 (December 2016) - Lansdowne, Krystal; Strauss, David; Scully, Christopher
Abstract Background The cacophony of alerts and alarms in a hospital produced by medical devices results in alarm fatigue. The pulse oximeter is one of the most common sources of alarms. One of the ways to reduce alarm rates is to adjust alarm settings at the bedside. This study is aimed to retrospectively examine individual pulse oximeter alarm settings on alarm rates and inter- and intra- patient variability. Methods Nine hundred sixty-two previously collected intensive care unit (ICU) patient records were obtained from the Multiparameter Intelligent Monitoring in Intensive Care II Database (Beth Israel Deaconess Medical Center, Boston, MA). Inclusion criteria included patient records that contained SpO2 trend data sampled at 1 Hz for at least 1 h and a matching clinical record. SpO2 alarm rates were simulated by applying a range of thresholds (84, 86, 88, and 90 %) and delay times (10 to 60 s) to the SpO2 data. Patient records with at least 12 h of SpO2 data were examined for the variability in alarm rate over time. Results Decreasing SpO2 thresholds and increasing delay times resulted in decreased alarm rates. A limited number of patient records accounted for most alarms, and this number increased as alarm settings loosened (the top 10 % of patient records were responsible for 57.4 % of all alarms at an SpO2 threshold of 90 % and 15 s delay and 81.6 % at an SpO2 threshold of 84 % and 45 s delay). Alarm rates were not consistent over time for individual patients with periods of high and low alarms for all alarm settings. Conclusion Pulse oximeter SpO2 alarm rates are variable between patients and over time, and the alarm rate and the extent of inter- and intra-patient variability can be affected by the alarm settings. Personalized alarm settings for a patient's current status may help to reduce alarm fatigue for nurses.